Inovasi Media Ular Tangga Tiga Dimensi sebagai Strategi Pembelajaran Interaktif untuk Meningkatkan Prestasi Belajar Siswa Sekolah Dasar - Intan Putri Kamilah; Jesi Alexander Alim; Zakiah Ulya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effectiveness of three-dimensional snakes and ladders media as an interactive learning strategy to improve elementary school students’ motivation and academic achievement. The research employed a quantitative experimental method with a pretest–posttest design involving 28 sixth-grade students of SDN 147 Pekanbaru in the 2025/2026 academic year. The instruments consisted of learning achievement tests (pretest and posttest) and student questionnaires covering motivation, material comprehension, interaction, learning atmosphere, and media practicality. The results revealed a significant improvement from the average pretest score of 52 to the posttest average of 82.14, with the Wilcoxon test showing a significance value of 0.000 (<0.05). Furthermore, most students responded positively to the media, as it enhanced enthusiasm, facilitated material understanding, encouraged collaboration, and created an enjoyable learning environment. These findings confirm that the three-dimensional snakes and ladders media not only improves academic outcomes but also supports students’ affective and social development. Therefore, this media is considered a feasible innovative alternative for elementary learning, although its use should be adjusted to the available time to achieve optimal results.